A review on development of placental transfusion in term and preterm infants - Lu, Jiangyi; Yue, Guang; Wang, Qianying; Zhou, Xiaofeng; Ju, Rong (Frontiers in Pediatrics, 2022)
In recent years, it has been verified that placental transfusion can replenish blood volume of neonates, improve organ perfusion in the early postnatal stage, and facilitate the transition from fetal circulation to adult circulation. Meanwhile, placental transfusion can reduce the need for blood transfusion and the onset of intraventricular hemorrhage, necrotizing enterocolitis, bronchopulmonary dysplasia, and other complications. Furthermore, it can improve the iron store and the long-term prognosis of central nervous system, and reduce infant mortality. Different methods have been used, including delayed cord clamping, intact umbilical cord milking, and cut umbilical cord milking. The World Health Organization (WHO) and other academic organizations recommend the routine use of delayed cord clamping at birth for the most vigorous term and preterm neonates. However, details of placental transfusion should be clarified, and the short/long-term impacts of this technology on some infants with special conditions still require further study.